An exploratory cross-sectional study of the impact of farm characteristics and calf management practices on morbidity and passive transfer of immunity in 202 Chianina beef-suckler calves. Issue 1 (1st January 2021) - Pisello, Lorenzo; Sala, Giulia; Rueca, Fabrizio; Passamonti, Fabrizio; Pravettoni, Davide; Ranciati, Saverio; Boccardo, Antonio; Bergero, Domenico; Forte, Claudio
Abstract: There are no published data on the risk factors associated with morbidity, mortality and passive transfer failure in Chianina beef-suckler calves. To implement prevention strategies in beef enterprises, gaining management information and identifying risk factors are essential. This cross-sectional study aimed to identify calf-level management practices and farm characteristics associated with disease incidence, mortality and serum IgG concentration in Chianina beef-suckler calves from farms in Umbria, Italy. In total, 202 Chianina beef-suckler calves aged 2–7 days from nine farms were enrolled. For each calf born, blood samples were collected and specific information on management practices and farm characteristics was obtained through farmer interviews. Serum immunoglobulin concentrations were measured using radial immunodiffusion. Mortality and morbidity data were extracted from the farm's cow file six months after the last farm visit. The impact of farm characteristics and calf management practices on the mortality rate could not be assesses due to low case fatality in our enrolled calves (10/202). A multivariable logistic regression model indicated that prepartum vaccination against Escherichia coli, rotavirus and coronavirus, and bottle-fed colostrum were associated with serum IgG concentration. Birth season and serum IgG concentration were associated with the development of neonatal calf diarrhoea and the development of both neonatal calf diarrhoea and respiratory disease, respectively. Furthermore, family-owned farms represent an important factor related to respiratory disease episodes. The possible influence of these factors on passive immunity and neonatal calf diarrhoea and respiratory disease appearance should be considered when advising farmers. Highlights: Effects of farm characteristics and management practices on health were investigated in 202 Chianina calves. Dam vaccination against Escherichia coli, Rotavirus and Coronavirus, and colostrum feeding assistance affect calf passive immunity. Calves with low serum IgG concentrations became sick; diarrhoea was common during cold months; respiratory disease was more common in family-run farms.